From the Politics of Recognition to the Politics of Resentment - Mariana de Gainza (Journal of Spinoza Studies)
Axel Honneth’s response to the objections that his theory of recognition has received from Althusserian-inspired perspectives invites us to consider what Honneth calls an insurmountable “social-ontological” difference. Insofar as it is Spinoza’s ontology that is at the basis of Althusser’s theory of ideology, we seek in this article to explore some of the problems that arise from the association of Spinoza’s thought with a philosophy of recognition. The concern at the basis of this essay is the way in which the absence of recognition and contempt tend to spread in the current global conjuncture.